ADOPTING PESANTREN-BASED JUNIOR HIGH SCHOOL PROGRAMS: THE PESANTREN CHANGE ITS EDUCATIONAL SYSTEM WITHOUT CONFLICT - Zainal, Suadi; Prasetyo, Muhammad Anggung Manumanoso; Yaacob, Che Mohd Aziz; Jamali, Yusra (Universitas Islam Negeri Ar-Raniry, 2022)
Some Islamic Boarding Schools (Pesantren) have integrated school education into its education system to generate excellent Muslims in science and technology. However, in practice, pesantren usually consider the school education as the second. Due to that, the santris are less motivated to learn science and technology, then results in them being unqualified. Responding to this problem, the government of Indonesia has made a policy to implement school education in pesantren, known as the pesantren-based junior high schools program (SMP-BP). This study examines the strategy of pesantren in managing junior high schools and explains the approach to adopting the SMP-BP. Our exploration utilizes a qualitative research design with a survey approach. Data were collected and analyzed using an analytical approach. The results showed that the SMP-BP program was carried out through problem analysis and strategic management. Problem analysis comprises human resources problems (santris and teachers) and evaluation methods. Furthermore, strategic management consists of: (1) curriculum development and integrated learning, (2) governance policy, (3) human recourses, (4) infrastructure and facilities, (5) finance, and (6) educational output. Our finding confirms that pesantren has changed its system to implement the SMP-BP program without any conflicts. This study can assist educational practitioners in their efforts to improve the quality of Islamic education in science and technology.